Analisis Kepuasan Pengguna Di Kota Makassar Terhadap Kualitas Website MyLPGO Menggunakan Metode Webqual 4.0 - Devi Chungiarto; Moh. Sofyan S. Thayf; Husni Angriani (KHARISMA Tech, 2021)
LPGO is an online shopping for liquefied natural gas in Makassar but the information provided by the application to users was still minimal. With the establishment of MyLPGO website, it can help users to know about the application better, because the website provides information about partners LPGO, how to application use, help centers, etc. However this website is still in a new category in society, so research is needed to analyze user satisfaction in Makassar about website that has been presented. The webqual 4.0 method develop by Stuart Barners dan Richard Vidgen can be used to measure user satisfaction with three main variables studied, namely usability quality, information quality, service interaction quality. Based on the results of data collection using a questionnaire with 83 repondents and testing data with multiple linear regression using SPSS 25, the result show that information quality and service interaction quality have a positive effect on user satisfaction but usability quality does not have a positive effect on user satisfaction. So that the developers need to apperance of the website that was presented to make it look more professional dan activities on the website can be futher improved. This research focuses on the quality of the MyLPGO website peceived by users anda what thing developers need to consider to increase user satisfaction.